High performance athletes` education: value, challenges and opportunities - Pavlidis, G.; Gargalianos, D. (Journal of Physical Education and Sport, 2014)
The purpose of this paper is to investigate the value of education for High Performance Athletes, the challenges they face when they try to combine a career in sport with education and the opportunities available to educate themselves. The Socio-Ecological Model was applied to contextualize factors that inhibit their effort to get an education. It was found that such factors could be at individual, interpersonal, institutional and community levels, as well as state policies. However, the literature supports the argument that as life extends beyond a sporting career High Performance Athletes need to understand the value of education and by implementing a dual career strategy prepare themselves for the challenges of life when sport cannot be practised any more.